Plano conceitual para Vitrine de Inovação do Instituto Federal de Brasília à imprensa - Soares, Renata Monteiro (2021)
Among researchers, professors and students at the Federal Institute of Brasília (IFB), concepts such as knowledge, innovation and creative economy are common in academic daily life. Technologists and technicians courses are offered in the areas of Food, Agriculture, Agroecology, Environmental Control, Electromechanics, Electronics, Events, Furniture, Information Technology, Clothing, among others - and educational, research and extension experiences demand more and more visibility, recognition and economic projection. The purpose of this study is to develop a conceptual communication plan for the IFB's Innovation Showcase - a dialogical digital platform available on the web, from the perspective of scientific dissemination to the press and that provides interaction and the meeting of common audiences. Specifically, address the relationship between researchers and the press and, and understand the dissemination of results in scientific dissemination. With the challenge of placing itself as a creative laboratory and, in movement, in a relationship between academia, scientific research and society. An environment for the circulation of information, where it is possible to present innovative service and production methods; awakening to new scientific possibilities and; bring together different actors in favor of scientific dissemination.